PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIIIA2 MTs DARUL HIKMAH PEKANBARU - Siti Aisyah Syahrul; Atma Murni; Syarifah Nur Siregar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aimed to improve the learning process and improve the student’s Mathematical Problem Solving Skill (MPSS) by applied Problem Based Learning (PBL) model. This study was Classroom Action Research with two cycles. This research conducted of class VIIIA2 MTs Darul Hikmah Pekanbaru on first semester of academic year 2018/2019 wich consists of 28 female students with heterogeneous academic. The instruments used in this research were learning instruments and the instruments of collecting data. The learning instruments used include syllabus, lesson plan, and student work sheets, while the instruments of collecting data were observation sheets and MPSS test. After analysis of implementing the PBL model on students and teacher activity, the implementation of PBL mades students who are initially lazy and don’t want to try solving the problem became more interested in learning because the problem presented were related to daily life. The MPSS test data of analyzed students’ activity shows an improvement. In first test, three students were in low qualification and 25 students were in very low qualification. In first cycle the number of students in both qualifications decreased to 1 and 2 students respectively. In second cycle there are no more students who were in low qualification and very low qualification. Based on data analysis, it can be concluded that the implementation of PBL can improve learning process and student’s MPSS at class VIIIA2 MTs Darul Hikmah Pekanbaru.Key Words: problem based learning, mathematical problem solving skill, learning process